Evaluation of dropout reason from addiction treatment - Vardar, Erdal; Sönmez, Bülent; Şıpka, Hüseyin; Karaca, Ebru (Journal of Dependence, 2015)
Objective:Remission rates among patients with alcohol and substance addictions are low. Dropout of treatment, which can be referred to as relapse, is an unresolved issue in addiction therapy. In this study, we evaluated the treatment dropout reasons of inpatients with substance addictions in the Trakya University, Balkan Addiction Research and Treatment Unit. Method: 130 patients receiving inpatient addiction treatment during the course of one year were included in this study. The patients’ socio-demographic characteristics and substance use characteristics related to their addictions were retrospectively evaluated with the assistance of a questionnaire and the Addiction Profile Index Scale (API). Upon admission, patients received both written and verbal information regarding the recommended 28-day treatment program. Those who agreed to follow the treatment formed the study sample. The data from the 70 patients who dropped out of the treatment program were compared with those from the 60 who finished their treatment. This study set out to evaluate the psychological and social factors that lead treatment program participants to discontinue treatment. Results: Of the 130 alcohol and substance addicted patients that participated in the study, 60 patients (46.2%) completed the 28-day treatment program. The mean age of those who completed their treatment was 38.2±14.1 years, while it was 31.8±9.5 years for the drop-out patients, a statistically significant difference. There was no remission in 78.5% of the patients and for 61.5% of the patients; this was their first inpatient treatment. The dropout rates in opiate and alcohol addicted patients were 20.7% (n=6) and 45.7% (n=21), respectively. The dropout rates for cannabis and poly substance users were higher than the others and statistically significant. The mean age for beginning tobacco use among dropout patients was 14.6±4.5, while it was 16.1±3.3 among those who completed treatment, which is statistically significant. The dropout rate was significantly higher among patients with low anger management level as determined by API. Conclusion: The dropout rate among cannabis users, synthetic cannabis users, and poly substance users was higher. Other related issues were early tobacco use and lower anger management level. Attention to these factors during addiction treatment could reduce instance of relapse.